PENGGUNAAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V MIN TUNGKOB ACEH BESAR - Anisah; Setia Ningsih; fajriah (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2019)
Abstract In the learning process, the ability to understand a learning concept is influenced by the learning methods and models in accordance with the material to be taught, so as to facilitate students in understanding the material delivered by the teacher. The inquiry learning model is a learning model that is centered on the ability of students to find the real problem in the process of searching or investigating so that students must direct all their thoughts and skills to get new findings from each problem through the research process. This study aims to determine the activities of teachers, student activities, and determine student learning outcomes after using the inquiry learning model on the material volume of cubes and beams. The subjects of this study were 36 students in MIN Tungkob Aceh Besar, with a total of 36 students. This research uses Classroom Action Research (CAR). This research instrument uses observation sheets of teacher and student activities, as well as test questions. Then this data is analyzed using the percentage formula. The results obtained by teacher activity increased from the percentage value of 71.87% in the first cycle to 93.75% in the second cycle. Student activity from a percentage of 69.73% in the first cycle to 92.64 in the second cycle. Student test results using the inquiry model in the first cycle 38.89% increased to 80.56% in the second cycle. Based on the results of the study it can be concluded that by applying the inquiry learning model students are more active, systematic, critical, logical, analytical in understanding the concept of learning because students' talents and creativity can be sharpened well and they are given responsibility in determining their own problems. Keywords: Inquiry Model, Student Learning Outcomes Abstrak Dalam proses pembelajaran, kemampuan dalam memahami suatu konsep pembelajaran di antaranya dipengaruhi oleh metode dan model pembelajaran yang sesuai dengan materi yang akan diajarkan, sehingga dapat memudahkan siswa dalam memahami materi yang disampaikan oleh guru. Model pembelajaran inkuiri adalah suatu model pembelajaran yang dipusatkan pada kemampuan siswa dalam menemukan masalah yang sebenarnya dalam proses mencari atau menyelidiki sehingga siswa harus mengarahkan seluruh pikiran dan keterampilan untuk mendapatkan temuan-temuan baru dari setiap masalah melalui proses penelitian. Penelitian ini bertujuan untuk mengetahui aktifitas guru, aktivitas siswa, dan mengetahui hasil belajar siswa setelah menggunakan model pembelajaran inkuiri pada materi volume kubus dan balok. Subjek penelitian ini adalah siswa kelas MIN Tungkob Aceh Besar yang berjumlah 36 siswa. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Instrumen penelitian ini menggunakan lembar observasi aktivitas guru dan siswa, serta soal tes. Kemudian data ini dianalisis dengan menggunakan rumus persentase. Hasil penelitian yang diperoleh aktivitas guru meningkat dari nilai persentase 71,87% pada siklus I menjadi 93,75% pada siklus ke II. Aktivitas siswa dari nilai persentase 69,73% pada siklus I menjadi 92,64 pada siklus ke II. Hasil tes siswa dengan menggunakan model inkuiri pada siklus I 38,89% meningkat menjadi 80,56% pada siklus ke II. Berdasarkan hasil penelitian dapat disimpulkan bahwa dengan menerapkan model pembelajaran inkuiri siswa lebih aktif, sistematis, kritis, logis, analitis dalam memahami konsep belajar karena bakat dan kreatifitas siswa dapat diasah dengan baik dan mereka diberikan tanggung jawab dalam menentukan masalahnya sendiri. Kata Kunci: Model Inkuiri, Hasil Belajar Siswa